2001
DOI: 10.1203/00006450-200111000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Respiratory Function in Postnatal Lambs after Placental Insufficiency and Intrauterine Growth Restriction

Abstract: Epidemiologic studies have shown persistent effects of low birth weight on respiratory function and lung health, but underlying mechanisms are not understood. Our aim was to determine the effects of intrauterine growth restriction (IUGR), a major cause of low birth weight, on postnatal respiratory function. IUGR was induced by umbilico-placental embolization during late gestation in chronically catheterized sheep. Umbilicoplacental embolization was performed between 120 d of gestation and term (~146 d) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 44 publications
3
65
1
1
Order By: Relevance
“…After 3-5 d of fixation (for future histologic analysis), the right LV was determined using the Cavalieri method (22). Pulmonary DNA and soluble protein concentrations in lung tissue were determined using established fluorometric DNA and colorimetric protein assays (23).…”
Section: Methodsmentioning
confidence: 99%
“…After 3-5 d of fixation (for future histologic analysis), the right LV was determined using the Cavalieri method (22). Pulmonary DNA and soluble protein concentrations in lung tissue were determined using established fluorometric DNA and colorimetric protein assays (23).…”
Section: Methodsmentioning
confidence: 99%
“…uteroplacental embolization in pregnant ewes, caused impairments in bronchial growth (27) at birth and significantly reduced functional residual capacity, total lung capacity at 30 cm H 2 O, diffusing capacity of the lung for carbon monoxide, and compliance of the respiratory system from birth to 8 wk of postnatal age in lambs (28). Moreover, gas exchange surface area, oxygen uptake, and body weight are strongly correlated in mammals (29).…”
Section: Lung Growth In Growth-restricted Rat Pupsmentioning
confidence: 99%
“…For example, studies in sheep have found that IUGR results in fewer, larger alveoli with thicker alveolar septa, and therefore impaired blood-gas exchange, which persists into adulthood (10,11). Functionally, these structural lung effects in IUGR sheep are reflected by reduced lung compliance and increased chest wall compliance in sheep-changes that may compromise respiratory function (12).…”
mentioning
confidence: 99%